2009
DOI: 10.1007/s12194-009-0068-z
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of electron beams collimated with a dual electron multileaf collimator: a feasibility study

Abstract: Electron applicators and cut-outs have been used for some time in the delivery of electron beam therapy. A dual electron multileaf collimator (eMLC) consisting of upper and lower eMLCs was designed, and dose distributions of electron beams delivered by it were evaluated by Monte Carlo simulations by use of the EGSnrc Monte Carlo code. The percentage depth dose (PDD), dose profiles, dose gradient falloff (G), depth of maximum dose (R(100)), surface dose, bremsstrahlung background, beam flatness, and penumbra of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…The applicator was completely replaced by the dual eMLC and simulated by the EGSnrc Monte Carlo code. The detailed design of the dual eMLC has been described elsewhere [7], where it was shown that the dose parameters [percentage depth dose (PDD), dose profiles, depth of maximum dose (R 100 ), dose gradient fall-off (G), surface dose (D s ), bremsstrahlung background (D x ), beam flatness and penumbrae] of the simulated dual eMLC, simulated applicator and physical measurement with applicators hanging in its position on the LINAC head, were all in good agreement. However, for completeness, we present a summary of the design.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The applicator was completely replaced by the dual eMLC and simulated by the EGSnrc Monte Carlo code. The detailed design of the dual eMLC has been described elsewhere [7], where it was shown that the dose parameters [percentage depth dose (PDD), dose profiles, depth of maximum dose (R 100 ), dose gradient fall-off (G), surface dose (D s ), bremsstrahlung background (D x ), beam flatness and penumbrae] of the simulated dual eMLC, simulated applicator and physical measurement with applicators hanging in its position on the LINAC head, were all in good agreement. However, for completeness, we present a summary of the design.…”
Section: Methodsmentioning
confidence: 99%
“…However, for completeness, we present a summary of the design. Figure 1 is a block diagram of the dual eMLC as proposed by Inyang and Chamberlain [7] and used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations